International Students in Azerbaijani Higher Education: Experiences and Support Mechanisms - Zeynalova, Ayisha; Mastieva, Elmira; Alizada, Tural; Ganjaliyeva, Vusala (ADA University, 2025)
In recent years, Azerbaijan has become an increasingly attractive destination for international students, welcoming learners from over 110 countries. This capstone project investigates the experiences of international students enrolled in Azerbaijani higher education institutions, with a specific focus on their cultural adaptation processes and the institutional support structures in place. Using a qualitative research design based on semi-structured interviews with thirteen international students, the study identifies key challenges encountered during their adaptation, including language barriers, cultural unfamiliarity, social isolation, and academic adjustment difficulties. Emotional reactions such as homesickness and impostor syndrome were also commonly reported, particularly during the initial phases of transition. Despite these challenges, many students developed coping strategies that helped them adjust to their new environment. These included forming social networks, participating in cultural and academic activities, learning the local language, and drawing on university-led support mechanisms. Orientation programs, peer mentoring initiatives, and accessible faculty were among the most effective institutional responses cited by participants. However, gaps were noted in the availability of structured language instruction, mental health services, and consistent intercultural engagement. This study contributes to the limited body of research on international student adaptation within the Azerbaijani context. It offers practical recommendations for universities and policymakers aimed at enhancing the inclusivity and effectiveness of student support systems. By highlighting the importance of both institutional responsiveness and student agency, the findings underscore the complex and evolving nature of cultural adaptation in higher education settings.
Keywords: International students -- Azerbaijan; Education, Higher -- Azerbaijan; Cultural adaptation -- Azerbaijan; Student support services -- Azerbaijan; Education